2020
DOI: 10.1038/s41598-020-64566-4
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Behaviors of Polyethylene/Silver Nanoparticle Composites: an Insight from Molecular Dynamics study

Abstract: cheng-tang pan 3 & tai-Ding You 3 this research uses molecular dynamics simulation (MD) to study the mechanical properties of pristine polyethylene (pe) and its composites which include silver nanoparticles (pe/Agnps) at two Agnp weight fractions of 1.05 wt% and 3.10 wt%. The stress-strain distribution of the tensile process shows that the embedded AgNPs can significantly improve the Young's modulus and tensile strength of the pristine PE, due to improvements in the local density and strength of the PE near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…(2) Improving the polymer matrix interaction with metallic NPs can result in better dispersion within the polymer. By integrating functional groups that align well with the NPs, you can enhance dispersion and strengthen the connection between the two materials [224]. (3) Utilizing optimized processing techniques like melt blending, solution mixing, or in situ polymerization can ensure the uniform dispersion of metallic NPs within the polymer matrix.…”
Section: Enhancement In Mechanical Strengthmentioning
confidence: 99%
“…(2) Improving the polymer matrix interaction with metallic NPs can result in better dispersion within the polymer. By integrating functional groups that align well with the NPs, you can enhance dispersion and strengthen the connection between the two materials [224]. (3) Utilizing optimized processing techniques like melt blending, solution mixing, or in situ polymerization can ensure the uniform dispersion of metallic NPs within the polymer matrix.…”
Section: Enhancement In Mechanical Strengthmentioning
confidence: 99%
“…According to a nanoindentation study of AgNPs by Dhriti Ranjan Saha et al, the modulus and hardness value showed 103.93 and 3.12 GPa [35]. The tensile strength of AgNPs is 87.32 MPa under 350 K temperature [36]. The mechanical properties of the conventional PMMA denture base material and AgNPs modified denture base materials are given in Table 1.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Inconsistent but larger grain sizes could be produced by increasing the concentration of Ag particles. According to the tensile test, crystallite grains or interconnection between the grains could play a major role in the tensile properties [86,87]. Although crystalline materials are stiffer due to grain-boundary-related hardening, other factors such as larger-sized of grains could lead to greater collisions between particles and consequently the breaking point [88].…”
Section: Mechanical Properties Of Si-ag Thin Filmsmentioning
confidence: 99%